1981
DOI: 10.1159/000123194
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic LH May Play a Role in Control of Pituitary LH Release

Abstract: We have recently reported immunoassayable luteinizing hormone (LH) in several areas of the rat brain and conspicuously present in the hypothalamus. In this report, we focus on the presence of LH in the hypothalamus and its potential role in regulation of pituitary LH release. In adult female rats, examined during the course of the estrous cycle, a significant fall in hypothalamic LH coincides with the surge in pituitary and serum LH at the time of proestrus, signaling ovulation. Ovariectomized adult rats show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 32 publications
4
36
0
Order By: Relevance
“…The authenticity of brain-derived β-FSH and β-LH is further shown by the absence of β-FSH and β-LH mRNA in the absence of reverse transcriptase in the RT-PCR mix, and by preadsorption tests in Western blot lanes and IHC brain-pituitary sections [11]. Additional evidence of de novo synthesis is supported by the persistence of pituitary hormones in the brain, including LH after hypophysectomy [2, 5]; the in vitro synthesis of pituitary hormones by hypothalamic tissue [6] and the localization of peptide and mRNA of pituitary hormones in the mammalian brain (PRL, GH, ACTH, MSH [5, 6]) and in the bonyfish brain (SL [7]). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authenticity of brain-derived β-FSH and β-LH is further shown by the absence of β-FSH and β-LH mRNA in the absence of reverse transcriptase in the RT-PCR mix, and by preadsorption tests in Western blot lanes and IHC brain-pituitary sections [11]. Additional evidence of de novo synthesis is supported by the persistence of pituitary hormones in the brain, including LH after hypophysectomy [2, 5]; the in vitro synthesis of pituitary hormones by hypothalamic tissue [6] and the localization of peptide and mRNA of pituitary hormones in the mammalian brain (PRL, GH, ACTH, MSH [5, 6]) and in the bonyfish brain (SL [7]). …”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, it was thought that LH and FSH were exclusively synthesized in vertebrate pituitary cells, but several years ago LH-like activity was detected in human median eminence extracts [1]. LH is also present in the rat hypothalamus, with a potential role in the regulation of pituitary LH release [2]. It was also shown that LH was present in the rat amygdala, septal area, thalamus, caudate nucleus and hippocampus [3].…”
Section: Introductionmentioning
confidence: 99%
“…Observa tions, recently reviewed [13,14], have led to a broadened concept of the way in which the central nervous system (CNS) functions. Pituitary hormones such as ACTH [12,17], alpha-MSH [2], growth hormone [17], prolactin [8], and luteinizing hormone (LH) [7], have also been reported to be present in the CNS. The anterior pituitary peptide, thyroidstimulating hormone (TSH), has been shown to be present in the rat median eminence at levels independent of circu lating TSH levels [1], Later the findings of extrapituitary TSH in the hypothalamus were attributed to contamination from retrograde blood flow from the anterior pituitary [16].…”
mentioning
confidence: 99%
“…Both content and concentration of LH in the nuclear pellet, Pi, were substantially lower. These findings provide further framework for speculation on the role of brain-based LH.We have previously reported the presence of immunoas sayable and bioassayable luteinizing hormone (LH) [7,8,13], growth hormone (GH) [11,13,20], and thyroid-stimulat ing hormone (TSH) [10,12,13] within certain areas of the rodent central nervous system (CNS) and have alluded to the origin [7,11,12], developmental profile [13], and possible role of these substances in neuroendocrine physiology [8], Using a sensitive and specific radioimmunoassay (RIA) for rat LH [7,8,13] and a standardized procedure for subcellu lar fractionation of neuronal tissue [4], we have found that particle-bound hypothalamic LH is preferentially asso ciated with synaptosomally rich fractions. Similar subcellu lar distribution has been reported for several CNS peptides including hypothalamic TSH [10] and melanocyte-stimulat ing hormone (MSH) [2].…”
mentioning
confidence: 78%
“…Parlow. There were several significant modifications from previously pub lished procedures (7,8]. Incubation with the first antibody was car ried out for 72 h instead of 24 h. The second antibody incubation was conducted for only 4 h instead of 24 h. It was established that the presence of sucrose in the RIA system did not interfere with the immunomeasurement of LH.…”
Section: Methodsmentioning
confidence: 99%